A Pattern-Based Approach to Manage Model References - Systa, Tarja; Jiang, Juanjuan (Electronic Communications of the EASST, 2009)
Model references play an important role in model integration, especially when models belonging to different domains are to be integrated. They are also needed in various model transformation tasks. In some cases, they need to be instantiated systematically, following certain rules. This calls for an instantiation specification of model references. In this paper we propose a pattern-based approach for modeling, specifying, and finally applying model references. We represent model references as so-called collaboration patterns, modeled as UML collaborations. We further describe the instantiation rules of collaboration patterns. A tool has been implemented for establishing the model references according to the specification, allowing the designer to assist in the process of semi-automated model reference instantiation. We demonstrate the usefulness of the approach and tools by applying them in designing Web service orchestrations.